2016
DOI: 10.4103/2230-8210.176360
|View full text |Cite
|
Sign up to set email alerts
|

Technetium uptake predicts remission and relapse in Grave's disease patients on antithyroid drugs for at least 1 year in South Indian subjects

Abstract: Context:Most of the information on remission related factors in Grave's disease are derived from Western literature. It is likely that there may be additional prognostic factors and differences in the postdrug treatment course of Grave's disease in India.Aim:To study factors which predict remission/relapse in Grave's disease patients from South India. Also to establish if technetium (Tc) uptake has a role in predicting remission.Subjects and Methods:Records of 174 patients with clinical, biochemical, and scint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
4
6
0
Order By: Relevance
“…Among the patients who reached the legal treatment duration, only 36% had a sustained remission. Our results are consistent with those reported of 32.7% in India [14], 46% in China [6] and 41.9% in Pakistan [15]. However, in Mexico Bolanos et al [12] reported a lower remission rate of 17.5%.…”
Section: Evolutionary Aspectssupporting
confidence: 93%
See 2 more Smart Citations
“…Among the patients who reached the legal treatment duration, only 36% had a sustained remission. Our results are consistent with those reported of 32.7% in India [14], 46% in China [6] and 41.9% in Pakistan [15]. However, in Mexico Bolanos et al [12] reported a lower remission rate of 17.5%.…”
Section: Evolutionary Aspectssupporting
confidence: 93%
“…However in the series of Cappeli et al [13] the goiter size and FT4 level were not predictive factors of the long-term prognosis. In the series of Shingai et al [14] in India, a higher Technetium uptake was found to be significantly associated with relapse.…”
Section: Evolutionary Aspectsmentioning
confidence: 84%
See 1 more Smart Citation
“…Higher initial TSH (p=0.007), smoking status (0.026), higher 99 m Tc uptake (p=0.05), and pharmaceutical hypothyroidism (p=0.023) were significantly associated with remission. The level of 99 m Tc uptake at initial presentation is reported to predict remission in a previous study as well (30). Similarly, smoking status and higher TSH levels are associated with remission (29).…”
Section: Discussionmentioning
confidence: 79%
“…Hyperthyroidism is the most common organ-specific autoimmune disease and the most important reason for Graves' ophthalmopathy ( 13 – 15 ). Although the pathogenesis of hyperthyroidism has not been completely elucidated, recent studies indicated that the change of immunologic function may be closely correlated with the occurrence of hyperthyroidism ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%